Pengaruh Layanan Bimbingan Kelompok Terhadap Peningkatan Pemahaman Self-Control Siswa - Yuliandita, Selvya; sugiyo, sugiyo (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
This study was conducted based on the phenomenon that occurs in class IX students of SMP N 1 Wanasari Brebes which led to a low negative behavioral symptoms associated with the understanding of self-control. The purpose of this study was to determine the effect of group guidance services to increase students' understanding of self-control. This type of research is experimental research. Experimental research is research used to search for a specific treatment effect. This study was conducted with eight times the provision of treatment on IXA grade students of SMP N 1 Wanasari Brebes, with research subjects 10 students. Data collection method used is the scale of self-control. Data were analyzed using descriptive analysis of the percentage and the Wilcoxon test. The results showed an effective learning behaviors of students categorized as moderate (55%). After being given a treatment through group guidance increased understanding of self-control students in the high category (81%). It shows that the effect of group guidance services to increase students' understanding of self-control.